Aktualisasi Islam Keindonesiaan Dalam Konteks NKRI - Firdaus Syam (Himmah: Jurnal Kajian Islam Kontemporer, 2020)
The role of Islam in Indonesia to the existence and survival of the Unitary State of the Republic of Indonesia (NKRI) has an important role, significant and strategic good in the past, present and future against the sovereignty of the state at least since the 4 (four) things that can be used as the basis of thinking that islam plays an important role in the sovereignty. Indonesia is a country is pluralist, in the context of social, political, and constitutional law are known by the term Bhineke Tunggal Ika. Muslims are the predominant majority to accept the diversity of it as the inevitability of the Destiny of Allah SWT. This then is understood as the message of the importance of tolerance, living side by side in a country that was founded together by means of a fair, humane and civilized. The charter of Medina is an example of the form of agreement in recognizing the existence of pluralism. In actualization, the first principle that says the Almighty God, That becomes evidence in a unifying pluralism in Indonesia.